Enhanced heat transfer in hybrid nanofluid: Role of suction and wedge angle on boundary layer dynamics - Zainal, Nurul Amira; Nazar, Roslinda; Zuberi, Haris Alam; Pop, Ioan (Universiti Kebangsaan Malaysia, 2025)
This study offers a numerical investigation of steady MHD flow and heat transfer characteristics of hybrid nanofluids past a permeable stretching/shrinking wedge. The study considers the effect of suction as well as an internal heat source. Similarity transformations are applied to convert the governing partial differential equations into a system of ordinary differential equations and solved numerically using MATLAB’s bvp4c function. The results reveal the existence of dual solutions for suction and shrinking parameters over certain ranges. Besides, the study also illustrates that increasing both the suction parameter and the wedge angle resulted in a higher Nusselt number which implies an enhancement in the heat transfer rate.